1989
DOI: 10.1042/bj2590785
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of parathyroid hormone receptors on dog kidney, human kidney, chick bone and human dermal fibroblast. A comparative study of functional and structural properties

Abstract: To evaluate the functional and structural characteristics of the parathyroid hormone (PTH) receptors on different tissues and the possible heterogeneity in structure and function, PTH receptors on dog kidney membrane, human kidney membrane, chick bone cell membrane and human dermal fibroblast membrane were evaluated. The results showed that human kidney plasma membrane, canine kidney plasma membrane and chick bone cell membrane possess one single class of PTH receptor with a Kd (dissociation constant) of 1-5 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…They could arise from intrinsic differences between hPTHR1s and opossum and rat PTHR1s, from differences in cellular PTHR1 expression or effector coupling or in the case of N-truncated fragments from PLC-independent PKC-activating mechanisms. To address these questions, we have measured the activation of membrane PKC activity by hPTH fragments in LLC-PK1 cells expressing hPTHR1s, for which adenylyl cyclase and PLC responses are known in detail and in a homologous human foreskin fibroblast system (fibroblasts have PTH/PTHrP receptors (17)(18)(19)(20)(21)(22) ). We will show that PLC-stimulating (14 -16) C-terminally truncated fragments such as hPTH(1-31)NH 2 and hPTH(1-28)NH 2 stimulate PKC activity as efficiently as hPTH(1-34)NH 2 in LLC-PK1 cells, whereas N-terminally truncated fragments that do not detectably stimulate IP 3 production in LLC-PK1 cells (14 -16) stimulate PKC activity in human fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…They could arise from intrinsic differences between hPTHR1s and opossum and rat PTHR1s, from differences in cellular PTHR1 expression or effector coupling or in the case of N-truncated fragments from PLC-independent PKC-activating mechanisms. To address these questions, we have measured the activation of membrane PKC activity by hPTH fragments in LLC-PK1 cells expressing hPTHR1s, for which adenylyl cyclase and PLC responses are known in detail and in a homologous human foreskin fibroblast system (fibroblasts have PTH/PTHrP receptors (17)(18)(19)(20)(21)(22) ). We will show that PLC-stimulating (14 -16) C-terminally truncated fragments such as hPTH(1-31)NH 2 and hPTH(1-28)NH 2 stimulate PKC activity as efficiently as hPTH(1-34)NH 2 in LLC-PK1 cells, whereas N-terminally truncated fragments that do not detectably stimulate IP 3 production in LLC-PK1 cells (14 -16) stimulate PKC activity in human fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…The elevated PTH levels are likely to be related to bone marrow fibrosis 10 11 12 13 . The induction of certain cytokines, such as interleukin-6 and tumour necrosis factor is also thought to be the alternate mechanism due to the elevated PTH levels 5 14 15 . Some studies have demonstrated that intact PTH has inhibitory effects on the growth of erythroid progenitor cells and erythropoietin synthesis 16 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that PTH is a potent stimulator of fibroblast proliferation [27]. It is speculated that osteoblasts respond to PTH to release paracrine factors such Igfs and Pdgfs that modulate adjacent fibroblastic cell types [28] considered to be preosteoblastic cells based on their location and expression of osteoblast marker proteins [29] and [30].…”
Section: Discussionmentioning
confidence: 99%